Simultaneous visual sustained attention-discrimination and goal-directed search are associated with excretion of catecholaminergic metabolites in children with attention-deficit/hyperactivity disorder - Llorente, Antolin M.; Voigt, Robert G.; Bhatnagar, Pooja; Jensen, Craig L.; Heird, William C.; Williams, Jane; D'Elia, Louis F.; Ager, Danielle; Satz, Paul (Journal of Pediatric Biochemistry, 2012)
The relationship between visual sustained attention-discrimination and goal-directed search was evaluated using a visual discrimination and exploration (goal-directed search) paradigm and urinary excretion of catecholaminergic metabolites [dopamine (DA) and norepinephrine (NE)] in 6–12 year-old children (n = 31) strictly selected and diagnosed with attention-deficit/hyperactivity disorder (ADHD) using diagnostic criteria and other objective indices. The Structured Clinical Interview (SCID) (DSM-IV) was used to formally diagnose ADHD in children. A cognitive laboratory test was used to assess visual sustained attention-discrimination and goal-directed search (Children Color Trails Test 1 and 2). Urinary excretion of DA and NE metabolites was measured via reversed high-pressure liquid chromatography (HPLC). Pearson product-moment correlations were used to investigate the relationship between visual sustained attention and goal-directed search and urinary catecholamine metabolites of DA and NE. The present findings revealed a positive and moderately significant relationship between visual sustained attention and visual exploration and catecholaminergic metabolite levels of NE and DA, according to expectation. Decreased visual sustained attention and goal-directed search was associated with decreased DA and NE metabolite levels. The present results are consistent with past research with children with ADHD and studies with primates examining the intricate and respective interaction between the Locus Coeruleus and visual sustained attention-discrimination and the Ventral Tegmental Area and goal-directed search (visual exploration) respectively modulated through NE and DA. Applied and theoretical issues associated with the present findings also are discussed addressing recent computer-generated analogues of action selection models within the context of the extant findings.
Keywords: Attention-deficit/hyperactivity disorder; children; dopamine; exploration; norepinephrine; urinary metabolites